Hyperbaric Oxygen Preconditioning Can Reduce Postabdominoplasty Complications: A Retrospective Cohort Study. Issue 10 (October 2019) - Friedman, Tali; Menashe, Shaked; Landau, Geva; Sherf, Matan; Wiser, Itay; Seligman, Yaakov; Friedman, Mony; Hadanny, Amir; Efrati, Shai; Heller, Lior
Abstract : Background: Hyperbaric oxygen therapy (HBOT) can improve wound healing and has been found to have positive preconditioning effects in animal models. Among esthetic surgical procedures, abdominoplasty poses the highest rate of postoperative complications. The aim of this study was to evaluate the effect of preoperative HBOT as a preconditioning treatment for expected postsurgical complications. Methods: We conducted a retrospective cohort study among patients who underwent abdominoplasty at our institute and private practice between January 2012 and November 2017. Patients who received preoperative HBOT were compared with patients who did not receive HBOT. Surgical complication data and demographic, preoperative and postoperative data from patient records were collected. Results: The study included 356 patients. Of them, 83 underwent HBOT preoperatively. Using preoperative HBOT, postoperative complications were significantly reduced from 32.6% (89 patients) to 8.4% (7 patients), P <0.001. Moreover, 17 (6.2%) patients in the comparison group and none in the HBOT group experienced necrosis ( P = 0.016). In the multivariate analysis, preoperative HBOT was an independent protective factor against postoperative complications (odds ratio, 0.188; 95% CI, 0.082–0.432; P < 0.001). After propensity score matching, the study results remained the same. Conclusions: Preoperative HBOT can reduce postoperative complication rate in abdominoplasty patients. Further prospective studies are necessary to validate the findings and characterize patients who benefit the most from this treatment. Abstract : Supplemental Digital Content is available in the text.